The intensive silvopastoral systems in Latin America sustainable alternative to face climatic change in animal husbandry - Murgueitio, E.; Barahona, R.; Chará, J. D.; Flores, M. X.; Mauricio, R. M.; Molina, J. J. (Cuban Journal of Agricultural Science, 2016)
The challenge of facing the climatic change in the Latin America animal husbandry is a global priority especially in tropical and subtropical regions. Although the expressions rate of this globalphenomenon forces to work quickly in adaptation agendas, it also advances in reducing the main causes (mitigation). In recently way the research and innovation look for productive models that combine mixed attributes of adaptation and mitigation in simultaneous way. One of these is the Intensive Silvopastoral System (ISPS) that has positive results which is already promoted in programs and alliance projects between governments, farmer institutions and institutions of international cooperation. These initiatives contribute to the environmental management of the territory occupied by animal husbandry (in many regions they occupy more than a third of theterritory) and can be a tool to reduce deforestation; they are good to rehabilitate degraded lands; increase the production of animal husbandry benefits with low demand of agrochemical and forest at the time that are generator of ecosystem services such as quality and quantity of water, biodiversity conservation and the greenhouse gas reduction. The Intensive Silvopastoral Systems (ISPS) are a use of land within the Livestock Agricultural Forestry Systems (LAFS)characterized by simultaneous applying several agro-ecological principles. They combine forage shrubs in high density for direct browsing; they use several tropical or subtropical grasses andwood tress species, palms or fruit trees. The ISPS uses rotational grazing with electric fences and tapes, and guarantees good water in mobile water trough and mineralized salt for cattle (milk, meat, dual purpose) and sheeps. This article provides an update synthesis on research conducted mostly in Latin America, which show an increase in meat and milk production with obvious attributes of sustainability.Key words: Intensive silvopastoral systems, sustainable animal husbandry, climatic change